2017
DOI: 10.1371/journal.pone.0189790
|View full text |Cite
|
Sign up to set email alerts
|

Acne keloidalis nuchae in Asian: A single institutional experience

Abstract: Acne keloidalis nuchae, a type of folliculitis involving the back of the neck, is common in black men, although rare cases have been reported in patients of other ethnicities. We analyzed the clinicopathological features of acne keloidalis nuchae in 17 Asians. Patients’ age at the time of presentation ranged from 20 to 69 years. Most patients experienced the disease over 2 years (range, 3 months–20 years); follow-up data were available for 11 (65%) patients (range, 2–95 months). Nine (53%) patients had comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 13 publications
1
23
0
1
Order By: Relevance
“…Regarding gender, patients consulting with AKN, FD and DCS were most frequently males, while patients consulting with traction alopecia, CCCA, FFA, FAPD and LPP were most frequently females, in accordance with the literature [7,9,[14][15][16][17][18][19][20]. The most frequent alopecias in both genders were AGA followed by AA.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding gender, patients consulting with AKN, FD and DCS were most frequently males, while patients consulting with traction alopecia, CCCA, FFA, FAPD and LPP were most frequently females, in accordance with the literature [7,9,[14][15][16][17][18][19][20]. The most frequent alopecias in both genders were AGA followed by AA.…”
Section: Discussionsupporting
confidence: 85%
“…Collagen fibers are like those in hypertrophic scarring rather than those in real keloids. Also, histopathological examination can reveal different stages of inflammation in one lesion (13).…”
Section: Discussionmentioning
confidence: 99%
“…Laser therapy should be considered for the hair removal and/or softening of the keloidal plaques (17,18). Several authors have reported that laser hair removal is an option to prevent relapsing folliculitis (13). If pustules and draining sinuses are present and bacterial culture is positive, oral antibiotics should be administered in addition to topical antibiotics (19).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, few cases of AK in women have been reported in the literature . AK in patients of other ethnicities, particularly Asian patients, is less common . AK normally develops from firm, skin‐colored papules and pustules most often on the occipital region of the scalp extending to the posterior region of the neck.…”
Section: Introductionmentioning
confidence: 99%